“Pipo and Mia, the magic knights”: Educational intervention to foster self-regulated learning in preschool - Silva Moreira, Janete; Costa Ferreira, Paula; Veiga Simão, Ana Margarida (Aprender, 2024)
Self-regulated learning (SRL) skills are transversal, relevant to the development of autonomy, and should be fostered from early childhood. Dynamic assessment allows us to assess and intervene simultaneously, identifying the learner’ potential. The sociocognitive model with cyclical phases was followed (i.e., forethought, performance, and self-reflection). The study aim was to contribute with new approaches to foster SRL in preschool. Specifically, the educational intervention “Pipo and Mia, the magic knights”, tested with 115 children (t-test analysis), and the professional training “Practices to promote SRL in preschool”, attended by nine teachers while developing the intervention with their groups. Results showed an improvement in the quantity and quality of the SRL strategies applied by children after the intervention. The professional training allowed teachers to learn about SRL, and reflect on their practices, contributing to improve them. Research implications are reinforced in theoretical terms, considering the three cyclical phases, when compared with research studying only one phase. Practical implications highlighted the innovative, ecologic, and contextualized contribution of the instruments now available, which are scarce to Portuguese preschool. They support the development of self-regulatory skills, preventing and intervening, in a universal approach.